Developing a Model for EFL Teachers' Problem-Solving Skills - Asnavi Qeshmi, Lamya; Afraz, Shahram; Samimi, Fazlolah (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The objective of this study was to investigate and model the problem-solving skills of Iranian EFL teachers through a mixed-methods design, aiming to develop a validated, context-specific framework for addressing classroom challenges.Methods and Materials: The study employed an exploratory sequential mixed-methods approach conducted in three phases: a qualitative phase, a pilot study, and a quantitative phase. In the qualitative phase, semi-structured interviews were conducted with 30 Iranian EFL teachers from private language institutes in Hormozgan Province to extract key themes related to their classroom problem-solving strategies. These themes informed the development of a 24-item Problem-Solving Skills Questionnaire (PSSQ), which was piloted with 50 teachers and then distributed to a larger sample of 200 teachers in the final phase. Confirmatory Factor Analysis (CFA) was conducted using LISREL, and reliability indices were computed via SPSS (version 20). Six core dimensions were assessed: setting clear expectations, establishing a positive learning environment, active listening, positive reinforcement, managing behavior, and collaborating with parents.Findings: The CFA confirmed the six-factor structure with excellent model fit indices (e.g., χ²/df = .722, RMSEA = .000, CFI = 1.00). All factor loadings were statistically significant (p < .001) and above .70, indicating strong item validity. Reliability was high across all subscales (α > .85), with total instrument reliability at .920. Among the six dimensions, active listening received the highest mean score, followed by positive reinforcement and managing behavior, while collaborating with parents and establishing a positive learning environment scored lowest.Conclusion: The study offers a robust model of EFL teachers’ problem-solving skills in the Iranian context and highlights both strengths and areas for development. Emphasis on communicative strategies like active listening suggests cultural alignment, while lower emphasis on parental collaboration and classroom climate points to potential gaps in teacher training and institutional practice.